Short flowers for long tongues: Functional specialization in a nocturnal pollination network of an asclepiad in long-tongued hawkmoths - Amorim, Felipe W. [UNESP]; Marino, Salvador; Sanz-Veiga, Priscila Andre [UNESP]; Ollerton, Jeff; Oliveira, Paulo Eugênio (Wiley, 2022)
Since Darwin, very long and narrow floral tubes have been known to represent the main floral morphological feature for specialized long-tongued hawkmoth pollination. However, specialization may be driven by other contrivances instead of floral tube morphology. Asclepiads are plants with a complex floral morphology where primary hawkmoth pollination had never been described. We detailed here the intricate pollination mechanism of the South American asclepiad Schubertia grandiflora, where functional specialization on long-tongued hawkmoth pollinators occurs despite the short floral tube of this species. We studied two plant populations in the Brazilian Cerrado and recorded floral visitors using different approaches, such as light-trapped hawkmoths for pollen analysis, direct field observations, and IR motion-activated cameras. Finally, using a community-level approach we applied an ecological network analysis to identify the realized pollinator niche of S. grandiflora among the available niches in the pollinator community. Throughout a period of 17 years, long-tongued hawkmoths were consistently recorded as the main floral visitors and the only effective pollinators of S. grandiflora. Flowers rely on highly modified corona and gynostegium, and enlarged nectar chambers, to drive visitors and pollination mechanism. Despite its relative short-tube, network analysis placed S. grandiflora in the module including exclusively long-tongued hawkmoth pollinators and the most phenotypically specialized sphingophilous plants in the community. These results represent the first example of functional specialization in long-tongued hawkmoths in an asclepiad species. However, this specialization is uncoupled from the long floral tubes historically associated with the sphingophily syndrome. Abstract in Portuguese is available with online material.
Keywords: Apocynaceae; Asclepiadoideae; Cerrado; ecological networks; floral specialization; hawkmoth pollination; nectar; pollinator niche